The Fermentation of Green Algae (Spirogyra majuscule Kuetz) using Immobilitation Technique of Ca-Alginate for Saccharomyces cerevisiae Entrapment - Atmanto Heru Wibowo; Lailatul Mubarokah; Adhitasari Suratman (Indonesian Journal of Chemistry, 2013)
A study of batch fermentation of green algae (Spirogyra majuscula Kuetz) from Pengging Lake, Boyolali, Central Java for bioethanol source using immobilization technique of Ca-alginate for Saccaromyces cerevisiae entrapment has been done. The scope of the study emphasized on the best condition for the processes of hydrolysis and fermentation. Concentration of sulfuric acid and hydrolysis time were varied with 0.1, 0.2, 0.3, 0.4 and 0.5 M for 30, 90, 150, 210, 270, 330, 360, 390, 420, and 450 min to obtain the maximum glucose content of UV analysis. Na-alginate : yeast ratio and fermentation time were varied with 1:5, 2:4, 3:3, 4:2 and 5:1 (w/w) for 1, 2, 3, 4, 5, 6 and 7 days. Distillation at 70-80 °C was deployed to purify the fermentation product. The ethanol content in the product was analyzed using gas chromatography-flame ionization detector (GC-FID). The result of study showed that maximum glucose content was obtained 2.1% from 0.2 M sulfuric acid for 6 h of hydrolysis. Maximum ethanol content was obtained 54.1% from 2:4 ratio of Na-alginate : yeast (w/w) for 4 days of fermentation. The study also concludes that immobilization technique of Ca-alginate increase alcohol content compared to without immobilization of green-algae fermentation.